"A Trivial and Unimportant Ally"? Britain and the West German-Soviet Treaty Negotiations, 1970. Issue 3 (3rd July 2019) - Nannichi, Ken
ABSTRACT: This analysis explores British perceptions and roles regarding the negotiation of the West German-Soviet Moscow treaty of 1970. Whilst supportive of West German Ostpolitik, Britain has received a very marginal role in the historiography of the treaty. By exploring the consultation process in the so-called Bonn Group of the United States, Britain, France, and West Germany, this exegesis explains that Britain played a leading role in building consensus and forming schemes to resolve the issue of the treatment of Quadripartite Rights and Responsibilities concerning Berlin in the Moscow treaty package. As background, this essay also explains the policies of the Harold Wilson's Labour government and Edward Heath's Conservative government regarding European détente in Europe, including West German Ostpolitik .